Impact Assessment of Culinary Tourism Potential on the Revitalization of Post-Pandemic Marine Tourism at Mampie Polewali Mandar Beach, West Sulawesi: A Qualitative Analysis - Wim J Winowatan Winowatan; I Putu Suarta; Rita Rita (Newinera Publisher, 2023)
The objectives of this study were (1) to find out what culinary potential can support post-pandemic covid 19 marine tourism on the Mampie Polewali Mandar beach, West Sulawesi. (2) to find out the culinary potential to support post-covid 19 pandemic marine tourism on the Mampie Polewali Mandar beach West Sulawesi. The research method used is research with qualitative data types with data collection techniques using interviews, documentation and observation then analyzed using qualitative descriptive analysis techniques. The research results show that there are actually a lot of culinary potentials, including by utilizing traditional specialties as one of the products that can be marketed or sold in the marine tourism area of Mampie Beach, apart from that by working with the local community to provide products, currently there is no culinary being utilized. so that the Mampie Beach marine tourism is not maximal yet so that it is not optimal in providing facilities and infrastructure for a marine tourism, especially considering that now we are in post-pandemic Covid 19 where tourists will feel bored doing activities that have been carried out from home and will traveling for vacation purposes. The lack of culinary potential as a support for marine tourism makes this known culinary potential that it turns out that the lack of initiative from the community, stakeholders to the local government means that marine tourism will also run as usual without any other additional income. This is due to the lack of information obtained by managers regarding what are the things that can support marine tourism, especially in increasing income, such as culinary tourism which will actually be a supporting factor for marine tourism in Mampie Beach, especially during the post-covid pandemic 19 at the moment.